Body Osteotomıes (Reports Of 13 Cases) - Orhan Güven; Nihat Tuncer (Galenos Yayinevi, 1995)
Mandibular body osteotomies are indicated at the correction of selected cases of; the mandibular prognathism, class III open-bite deformity, anterior crossbite in the adults, and bilateral or unilateral delated body fractures which were healed in malposition. Six major relationships must be evaluated in planning treatment for dentofacial problems; maxilla to cranium, mandilla to cranium, maxilla to mandilla, and maxillary teeth to maxilla, mandibular teeth to mandible, and maxillary teeth to mandibular teeth. Cephalometric analysis and orthognathic model surgery are necessary to evaluate other relationships. In this paper, evaluation of cephalometric analysis of preoperatif and postoperatif are presented for 13 patients who was performed body osteotomies.